STUDY OF RELATIONSHIP BETWEEN THE PROTEIN OXIDATION MARKERS AND ADIPOKINES IN OBESE TYPE 2 DIABETIC PATIENTS - SUKHPAL SINGH; AMITA MAHAJAN; JASPREET KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was done to explore the correlation if any, between obesity markers adiponectin, leptin, and protein oxidative stress (OS) status in obese with and without type 2 diabetic mellitus (T2DM) patients. Methods: In the present study, 30 healthy subjects, 30 obese non-diabetics, and 30 obese T2DM patients were enrolled. Protein OS parameters such as advanced oxidation of protein products (AOPPs) and protein carbonyl (PC) were estimated. Serum leptin, adiponectin, and insulin levels were measured by ELISA. Results: The AOPP, PC, leptin, leptin adiponectin ratio (LAR), insulin, and homeostasis model assessment of insulin resistance (HOMA-IR) levels were significantly higher in obese non-diabetic and obese T2DM as compared to healthy control (p<0.001). However, serum adiponectin levels were significantly lower in obese non-diabetic and obese T2DM as compared to control (p<0.001). HOMA-IR and LAR both the index of IR were increased in obese non-diabetic and obese T2DM. Positive correlations were observed for AOPP with body mass index, PC in obese non-diabetic and with fasting blood glucose, postprandial blood glucose, HOMA-IR, and PC in obese T2DM. A negative correlation was found between PC and adiponectin in obese non-diabetic and obese T2DM. A significant inverse correlation was obtained between leptin and adiponectin in obese T2DM only. Conclusion: The present study suggested that increased protein OS, hyperinsulinemia, and hyperleptinemia may lead to hypoadiponectinemia in obese with and without T2DM. Moreover, determination of protein oxidation markers can be useful for monitoring the dysregulation of adipokines and glucose metabolism in obesity and T2DM.